Laccases – enzymes with an unlimited potential - Szczęsna-Antczak, Mirosława; Benedykt Kaczmarek, Michał; Kwiatos, Natalia; Bielecki, Stanisław (Lodz University of Technology Press, 2017)
Laccases (EC 1.10.3.2) are among the few enzymes, the history of which dates back to the 19th century. These oxidoreductases are present in almost all known fungi, some species of higher plants and insects. Moreover, in recent years, these enzymes have also been found in some bacterial organisms. Due to their significant properties and structure of the catalytic centre, laccases have been classified as the multicopper oxidases (MCOs). These enzymes are able to catalyse the oxidation of phenolic and non-phenolic compounds, with the aid of small molecules referred to as mediators. Thanks to their diverse nature, laccases have gained attention of both scientists and entrepreneurs from all over the world. Their significance is reflected in countless scientific and industrial applications, wherein laccases have become inseparable from chemical syntheses, the food industry, textile industry, biosensor design and the environmental protection. This paper gathers the most important information and the latest scientific discoveries relating to this desirable biocatalyst.
Keywords: Laccases; multicopper oxidases; reactions; properties; applications; lakaza; oksydaza; reakcje; właściwości; zastosowanie